Pengaruh Perilaku Caring Perawat terhadap Peningkatan Kualitas Hidup Pasien Gagal Ginjal Kronik di Ruang Hemodialisa Rumah Sakit Royal Prima Medan - Yusrita Syafitri; Alvianis Duha; Andini Putri Meylani; Brigity Sephanie; Meilis Karina Anugrah Bako; Tiarnida Nababan (Universitas Malahayati Lampung, 2022)
ABSTRACT Chronic renal failure (CKD) is a pathophysiological process that results in a progressive decline in kidney function that leads to kidney failure. Based on data from the Global Burden of Disease (GBD), in 2017 there were 697.5 million cases of chronic kidney failure in the world. Hemodialysis as a replacement therapy for kidney function using a dialysis machine is widely chosen by patients with chronic kidney failure. The behavior of nurses in providing nursing care is closely related to the management of chronic kidney failure patients undergoing hemodialysis therapy. The purpose of this study was to determine the effect of nurse caring behavior on improving the quality of life of patients with chronic kidney failure in the hemodialysis room at Royal Prima Hospital, Medan 2022. This type of analytical study used a cross sectional design. The sampling technique in this study was purposive sampling with a total sample of 25 respondents. Based on the results of the Spearman test, s rho with p = 0.05, the results obtained are p-value (0.000) 0.05, then Ho is rejected. The conclusion is that there is a significant influence between the caring behavior of nurses and the quality of life of chronic kidney disease patients in the hemodialysis room of Royal Prima Hospital in 2022. Keywords: Caring Behavior, Quality of Life, Chronic Kidney Failure. ABSTRAK Gagal ginjal kronik (GGK) merupakan suatu proses patofisiologi yang mengakibatkan penurunan progresif fungsi ginjal yang berujung pada gagal ginjal. Berdasarkan data Global Burden of Disease (GBD), pada tahun 2017 terdapat 697,5 juta kasus gagal ginjal kronik di dunia. Hemodialisa sebagai terapi pengganti fungsi ginjal dengan menggunakan mesin dialisis banyak dipilih oleh pasien gagal ginjal kronik. Perilaku perawat dalam memberikan asuhan keperawatan sangat erat kaitannya dengan pengelolaan pasien gagal ginjal kronik yang menjalani terapi hemodialisa. Tujuan dari penelitian ini adalah untuk mengetahui adanya pengaruh perilaku caring perawat terhadap peningkatan kualitas hidup pasien gagal ginjal kronik di ruang hemodialisa Rumah Sakit Royal Prima Medan 2022. Jenis penelitian analitik menggunakan desain Cross Sectional. Teknik pengambilan sampel dalam penelitian ini adalah purposive sampling dengan jumlah sampel sebanyak 25 orang responden. Berdasarkan hasil uji Spearman, s rho dengan p = 0,05, di peroleh hasil nilai p-value (0,000) 0,05 maka Ho ditolak. Kesimpulannya adalah terdapat pengaruh yang signifikan antara perilaku caring perawat dengan kualitas hidup pasien penyakit ginjal kronik di ruang hemodialisa Rumah Sakit Royal Prima tahun 2022. Kata Kunci : Perilaku Caring; Kualitas Hidup; Gagal Ginjal Kronik.